Semantic and Grammatical Foundations of Double-Voicing - Avetisyan, Yuri (Bulletin of Yerevan University B: Philology, 2024)
In Armenian linguistics, the problem of voice shifts and double-voicing in the verb system has often been touched upon. The problems of the historical development of this phenomenon were considered and discussed, attempts were made to classify the directions of its formation and development, often expanding or narrowing the content and possibilities of the formation of this concept. A rich scientific literature has indeed been created on this issue. However, there are still disagreements not only on the issues already frequently discussed, but also on various manifestations of the subcategories of the grammatical category of the verbal voice, its interrelation, on the features of the expression of double-voicing at morphological and syntactic levels, etc. This article is devoted to the basics of the formation of voice shifts and double-voicing. The issue is investigated from the point of view of synchronic analysis and partially from the diachronic aspect.One of the richest subsystems of the verb system is the grammatical category of the verb voice. In the course of the historical development of a language, it often undergoes formative changes caused by a number of intra-linguistic and extra-linguistic factors: a lexical meaning change of the verb, the peculiarities of the verb using, the influence of variable language versions and foreign languages, the economy of communicative energy, incorrect constructions transmitted from spoken speech, etc. It is these factors or foundations that determine the nature and direction of the voice shifts (neutral > active, passive > neutral, and rarely, active > neutral) and the types of manifestation of double-voicing directly related to them: semantic doubleness, functional doubleness, doubleness of grammatical government. Both the mentioned fundamentals and the mentioned three types of double-voicing are discussed in detail in this article. Special attention is paid to clarifying the boundaries of the concept of double-voicing, and those manifestations of the relationship of subcategories (internal grammatical government of action, unique metaphorical use of a word, homonymy, etc.) that touch, but are not identified or should not be identified with double-voicing are highlighted.